Chapter 8 Asymmetries in the Italian regional system and their role model - PALERMO, Francesco (Taylor & Francis, 2021)
The multidimensional constitutional asymmetry in Italy includes several categories of regions: the special ones (each one with a very different degree of autonomy in terms of form of government, distribution, and use of legislative and administrative competences and financial arrangements), the ordinary ones negotiating additional legislative powers with the central government, and the remaining ordinary regions. In its first part, the chapter illustrates the trajectory and the current state of the art of the different forms of regional asymmetry in the Italian system, looking both at the legal and at the practical sides. It contends that asymmetry in the books looks way different than autonomy in action, due to a highly different implementation of the constitutional instruments by the various regions. In the second part, the chapter explores the contribution of Italian asymmetric design to the development of federalism/regionalism worldwide. As a matter of fact, all recent federal/regional experiments place asymmetry at their core. In most cases it serves the purpose to (try to) accommodate ethno-national differences, in a few others to deal with geographical or socio-economic disparities. These are the drivers of Italian asymmetry too. The Italian system has the comparative advantage of having been experimented with far longer than any other, being the oldest such constitutional experiment. For this reason, its achievements are of utmost importance for the current debate on (asymmetric) federalism and regionalism worldwide.